2020
DOI: 10.3892/etm.2020.9007
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of tolvaptan for fluid management after cardiovascular surgery: A systematic review and meta‑analysis of randomized control trials

Abstract: The purpose of this study was to systematically search the literature and analyze evidence from randomized controlled trials (RCTs) comparing tolvaptan with conventional diuretics for postoperative fluid management in cardiac surgery patients. An electronic search of PubMed, Scopus, BioMed Central, CENTRAL (Cochrane Central Register of Controlled Trials) and Google scholar databases was carried out up to 1st December 2019. Four RCTs were included. Tolvaptan was co-administered with conventional diuretics in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Here, no differences were seen in the potassium levels over time in the two groups, nor between the groups at the same same time point. A previous meta-analysis of serum potassium in patients on tolvaptan concluded that there was no difference in the mean serum potassium levels in patients with or without tolvaptan (23).…”
Section: Discussionmentioning
confidence: 97%
“…Here, no differences were seen in the potassium levels over time in the two groups, nor between the groups at the same same time point. A previous meta-analysis of serum potassium in patients on tolvaptan concluded that there was no difference in the mean serum potassium levels in patients with or without tolvaptan (23).…”
Section: Discussionmentioning
confidence: 97%
“…Here, no differences were seen in the potassium levels over time in the two groups, nor between the groups simultaneously. A previous meta-analysis of serum potassium in patients on tolvaptan concluded no difference in the mean serum potassium levels in patients with or without tolvaptan [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was listed as a health insurance drug in Japan in 2013 for cases of uid retention in liver cirrhosis for which conventional diuretics had insu cient clinical effects [8,9]. To date, the preventive administration of tolvaptan in patients who undergo cardiac surgery is found to be capable of controlling postoperative increase in body weight signi cantly, without indicating any side effects [10].…”
Section: Introductionmentioning
confidence: 99%